Perlindungan Data Pribadi di Indonesia Melalui Mekanisme Register of Processing Activities (ROPA): Studi Komparatif Antara UU PDP dengan GDPR (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The development of digital technology drives the urgent need for comprehensive personal data protection. This research examines the Register of Processing Activities (ROPA) mechanism through a comparative study between Indonesia's Personal Data Protection Law (PDP Law) and Europe's General Data Protection Regulation (GDPR). Using a normative juridical method and a comparative law approach, this research analyzes data protection regulations to identify differences and similarities in personal data protection mechanisms. The results of this study show that both regulations have similar goals in creating transparency and accountability, but have significant differences in implementation. Indonesia's PDP Law implements ROPA with a more flexible approach, while GDPR has stricter and more detailed provisions. In addition, this research also reveals the importance of ROPA as a documentation instrument that helps organizations manage data risks, protect individual rights, and build public trust in personal data management in the digital era. This study concludes that while ROPAs can enhance personal data protection, educational and technological support is needed for their effectiveness.